2019
DOI: 10.1002/acn3.714
|View full text |Cite|
|
Sign up to set email alerts
|

Hearing impairment after subarachnoid hemorrhage

Abstract: Background Subarachnoid hemorrhage (SAH) survivors experience significant neurological disability, some of which is under‐recognized by neurovascular clinical teams. We set out to objectively determine the occurrence of hearing impairment after SAH, characterize its peripheral and/or central origin, and investigate likely pathological correlates. Methods In a case‐control study (n = 41), participants were asked about new onset hearing difficulty 3 months post‐SAH, compared with pre‐SAH. Formal audiological ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…It affects younger people than other stroke types, resulting in a disproportionately high socio-economic impact due to loss of productive employment and the long-term healthcare burden [1]. Survivors of aSAH can suffer a wide range of neurological deficits ranging from physical disability to less obvious, yet life changing, sequelae including cognitive [2], psychological [3] and auditory deficits [4,5]. These disabilities contribute to unemployment following aSAH, with up to 50% of previously employed individuals not returning to work at 1 year following haemorrhage [6].Fatigue is another common consequence of aSAH with one analysis reporting a weighted mean fatigue frequency of 73.6% in the first year, falling to 50.7% thereafter, based on five published studies [7].…”
mentioning
confidence: 99%
“…It affects younger people than other stroke types, resulting in a disproportionately high socio-economic impact due to loss of productive employment and the long-term healthcare burden [1]. Survivors of aSAH can suffer a wide range of neurological deficits ranging from physical disability to less obvious, yet life changing, sequelae including cognitive [2], psychological [3] and auditory deficits [4,5]. These disabilities contribute to unemployment following aSAH, with up to 50% of previously employed individuals not returning to work at 1 year following haemorrhage [6].Fatigue is another common consequence of aSAH with one analysis reporting a weighted mean fatigue frequency of 73.6% in the first year, falling to 50.7% thereafter, based on five published studies [7].…”
mentioning
confidence: 99%
“…Although new onset hearing difficulty is common following aSAH, affecting up to 23% of survivors [10], impairing quality of life [28] and leading to unemployment [29], it is not routinely assessed and there are currently no recommendations for its management.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that APD underlies hearing difficulty following aSAH [3,10] and this understanding of the pathology is essential to guide ongoing management. There is no gold standard for the management of APD but a number of strategies can be considered including modification of the listening environment, technology (such as WRM, low-gain hearing aids or a combination), auditory training and compensatory strategies [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain volume on T1 sequences will be measured, since this has been shown to correlate with outcome 55. Cortical iron content will be assessed using quantitative susceptibility mapping after susceptibility weighted MR imaging, which predominantly measures siderotic iron deposits 56. Iron is a major component of Hb, and it is unknown what effects SFX-01, SFN or increased Hp binding of Hb may have on the downstream iron pathway.…”
Section: Discussionmentioning
confidence: 99%